Dermal substitution with Matriderm in burns on the dorsum of the hand - Ryssel, Henning; Germann, Günter; Kloeters, Oliver; Gazyakan, Emre; Radu, Christian Andreas (Burns, 2010)
Background - Dermal substitutes are used increasingly in deep partial and full-thickness burn wounds in order to enhance elasticity and pliability. In particular, the dorsum of the hand is an area requiring extraordinary mobility for full range of motion. The aim of this comparative study was to evaluate intra-individual outcomes among patients with full-thickness burns of the dorsum of both hands. One hand was treated with split-thickness skin grafts (STSG) alone, and the other with the dermal substitute Matriderm® and split-thickness skin grafts. - Material and Methods - In this study 36 burn wounds of the complete dorsum of both hands in 18 patients with severe burns (age 45.1±17.4 years, 43.8±11.8% TBSA) were treated with the simultaneous application of Matriderm®, a bovine based collagen I, III, V and elastin-hydrolysate based dermal substitute, and split-thickness skin grafting (STSG) in the form of sheets on one hand, and STSG in the form of sheets alone on the other hand. The study was designed as a prospective comparative study. Using both objective and subjective assessments, data were collected at one week and 6 months after surgery. The following parameters were included: After one week all wounds were assessed for autograft survival. Skin quality was measured 6 months postoperatively using the Vancouver Burn Skin Score (VBSS). Range of motion was measured by Finger-Tip-Palmar-Crease-Distance (FPD) and Finger-Nail-Table-Distance (FNTD). - Results - Autograft survival was not altered by simultaneous application of the dermal matrix (p>0.05). The VBSS demonstrated a significant increase in skin quality in the group with dermal substitutes (p=0.02) compared to the control group with non-substituted wounds. Range of motion was significantly improved in the group treated with the dermal substitute (p=0.04). - Conclusion - From our results it can be concluded that simultaneous use of Matriderm® and STSG is safe and feasible, leading to significantly better results in respect to skin quality of the dorsum of the hand and range of motion of the fingers. Skin elasticity was significantly improved by the collagen/elastin dermal substitute in combination with sheet-autografts.